The Yam Pukri youth forum - Ouédraogo, Sylvestre (Technical Centre for Agricultural and Rural Cooperation, 2004)
Sylvestre Ouédraogo describes how a youth forum on the Internet is broadening the horizons of young people throughout Burkina Faso.